Pinching pennies, costing dollars: Michigan's offender re-entry system - Dussia, Crystal A. (2015)
The current state of incarceration is a burden that every taxpayer bears. Through effective offender re-entry services, the financial, social, and physical burdens such as high crime rates, high recidivism rates, and the high cost of incarceration can be lessened for all citizens. Historical context establishes a foundation to be able to understand the current state of re-entry in Michigan as a small representation of the nation. The financial expenditures, social costs, and lack of evidence of past practice are explored. The content of this thesis is focused on Michigan within a national context of prison re-entry programs, history, and funding. Resources such as the Michigan Prisoner Re-entry Initiative, Michigan Department of Corrections (2013a, 2013b, 2013c) and churches were utilized in the review. The financial expenditures, social costs, and lack of evidence of past practice are explored. Overall, it is suggested that investment, support, and advocacy for offender re-entry is needed and beneficial